How Job Changes Affect People's Lives - Evidence from Subjective Well-being Data - Adrian Chadi; Clemens Hetschko (Center for Economic Studies and ifo Institute (CESifo), 2016)
For representative German panel data, we show that voluntary job switching leads to relatively high levels of life satisfaction, though only for some time, whereas the impact of exogenously triggered job changes is ambiguous. Risk aversion interacts negatively with this effect in life satisfaction. Analysing time-use data and well-being indicators for various areas of life, we find evidence that involuntary job mobility turns out to be harmful for satisfaction with family life. By linking this relatively new measure of family well-being to domestic events, such as future child births, our paper reveals a behaviourally valid predictor of great economic relevance.
Keywords: I31; J28; J61; J63; 330; life satisfaction; satisfaction with family life; job changes; honeymoon-hangover effect; employment protection legislation